PENGOBATAN DENGAN AL-QUR’AN : TELAAH ATAS PRAKTIK PENGOBATAN ALA TARIKAT NAQSABANDIYAH DI MINANGKABAU SUMATRA BARAT - Hakim, Lukman (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2023)
The Qur'an is believed to have a scientific nature, what is in the Qur'an is a scientific sign, not the scientific nature itself which is inherent in the Qur'an. The form of scientific cues of the Qur'an can be seen from a medical aspect. The theory and practice of health which was originally an assumption and then clinically examined in various laboratories, in fact found its relevance to the theories initiated by the Qur'an. Like the healing process practiced by the Naqsabandiyah Tariqah, this tariqa uses verses from the Al-Qur'an as a means to cure a disease. By combining the verses of the Qur'an with natural ingredients. This type of research is completely library research (library research) taking data from the literature that has something to do with the research theme. The analysis technique in this paper uses a content analysis model by exploring and analyzing the methods of treatment of the Tariqat Naqsabandiyah, especially those in West Sumatra.